(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
The article examines the musical context “Vertep” A. Liubchenko, theme of which is symphonic, polyphony, major, and minor synthesis mood. Akind of avant-garde artbecame anart laboratory that has accumulated in a figurative and associative thinking and logical model, synthesized painting, sculpture, architecture, literature, music and cinema. «Vertep» Arcadia Liubchenko as one of the works of avant-garde literature demonstrated polyphony, the synthesis of the arts. These are the kinds of genre sectionsnovella expressed titles: lyrical solo, romance, mystery, the session of the Indian tour, dance, puppet show, athletics. The musical structure is polyphonic sections of the work nature and read in the context of Ukrainian songs, the music world composers. Melody works by famous musicians – Vivaldi, Chopin, Mozart, Schubert and songs (rhythm and repeat phrases) organically intertwined into the fabric of the text “Vertep” shows world picture and the mood sections Novella. Music arabeskovist in works of A. Liubchenko expressed by decorated melodic pattern. Motive movement, life, winter, spring, fall, even numbers transmitted through music. The writer uses a variety of musical colors to transfer the world, the inner world of man and the glorification of industrialization, its new economic achievements. Each of the stories has its own mood, the musical tone associated with the musical fugue through orchestration enigma of the art world. The musical orchestration and synthesizes frames mood work defines the structure and musicality focuses on the “inner sound’” words.